2019
DOI: 10.3390/nu11071577
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions and Acceptability of Traditional Dishes Prepared with Provitamin A-Biofortified Maize and Sweet Potato

Abstract: Vitamin A deficiency (VAD) is prevalent in South Africa, particularly among predominantly poor rural communities. Provitamin A (PVA)-biofortified crops could be used to address VAD; however, there are challenges of poor consumer acceptability. This study investigated the effect of replacing white maize and cream-fleshed sweet potato (CFSP) with PVA-biofortified maize and orange-fleshed sweet potato (OFSP), respectively, on consumer acceptability and perceptions of traditional dishes of rural communities in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
2
11
0
1
Order By: Relevance
“…Finally, research has shown that there is a higher acceptance rate when nutritional information is provided along-side recommendations of introducing biofortified foods into the daily diet [ 98 , 99 ]. Thus, the combined effort of introducing biofortified crops together with the promotion of nutritionally diversified diets is encouraged [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research has shown that there is a higher acceptance rate when nutritional information is provided along-side recommendations of introducing biofortified foods into the daily diet [ 98 , 99 ]. Thus, the combined effort of introducing biofortified crops together with the promotion of nutritionally diversified diets is encouraged [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, un estudio llevado a cabo en una comunidad rural en Suráfrica mostró que hubo una percepción positiva en la preparación de platos tradicionales utilizando maíz y patata dulce biofortificados en provitamina A (Govender et al, 2019). En relación con la yuca, un reciente estudio demostró que había una mejor percepción por parte de los consumidores por la yuca amarilla que por la yuca de color blanco tradicional (Bechoff et al, 2018b).…”
Section: La Yuca Potencia En Calorías Pero Con Retos Nutricionales Frente a La Seguridad Alimentariaunclassified
“…In terms of the methods used and the evidence presented, less than half of the selected studies offer credible insights on outcomes, and many studies only provide descriptive insights on changes in the availability of processed and ultra-processed foods (e.g. Harris et al, 2020;Machado et al, 2018) or changes in intake of fortified foods (Govender et al, 2019;Khanh Van et al, 2014;Laurie et al, 2018).…”
Section: Evidence Base On Food Processingmentioning
confidence: 99%
“…First, one third of the processing papers focus on resource-driven food fortification activities that improve nutritional properties. Govender et al (2019) and Khanh et al (2015) show that food fortification needs to address consumer's acceptability before becoming successful. Looking at opportunities for upgrading of orange flesh sweet potato (OFSP) in South Africa, Laurie et al (2018) outlines that small-scale processors often face difficulties to meet the standards of the retailers' centralised procurement system in terms of food quality, quantity and safety.…”
Section: Appraisal Of Food Processing Studiesmentioning
confidence: 99%
See 1 more Smart Citation